PENGARUH FAKTOR PAJAK DAN FAKTOR-FAKTOR LAIN TERHADAP LEVERAGE PADA PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Pardosi, Ferdian (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2019)
Usage of debt can increase the value of the company, but with the consideration of potential financial distress the company will limited its total debt. To optimize the capital structure, the company must considered trade-off between gain of tax shield and loss from potential financial distress. The main purpose of this research was to test empirically, any factors that influence the leverage for there are still inconsistence research results from the prior study. Based on the data of the manufacture companies listed on Indonesia Stock Exchange (BEI), in addition of using tax factors that consisted of corporate tax rate, and non-debt tax shield, influencing the leverage, there are also another factors influencing the debt, which are investment opportunity set, profitability, and past debt. The whole analysis of this study based on the theory of structure of capital and the theory of the firm. The analyzed data are the combination of time series and cross-section data or panel data, utilizing the regression model supported by the software SPSS 20 on 0,05 or 5% of significance level. The result of the study shows that at the significance level of 0,05, investment opportunity set (0,006) and past debt (0,000) has significant positive effect on the leverage. While the corporate tax rate (0,721), non-debt tax shield (0,133) has no significance effect for the leverage at the significance of 0,05. While profitability (0,000) negatively has significance effect for the leverage at the significance of 0,05